Relación de altura total y comercial con el diámetro de los árboles en un bosque de colina baja del fundo Alcala, distrito de Punchana, Loreto, 2022 - Diaz Saquiray, Juan Carlos (2023)
The relationship of total and commercial height with the diameter of the trees was determined in a low hill forest, Punchana district, Loreto, Peru. Data from the forest census of commercial species from the Forest Management Unit (UMF) was evaluated for permits for the use of timber resources. The results indicate that the cubic type distribution model fits the average total diameter-height ratio Y= 6,488 + (0,669 x DAP) + (-0,009 x DAP2) + (4,195E-5 x DAP3)) and diameter- average commercial height Y= 3,488 + (0,513 x DAP) + (-0,007 x DAP2) + (3,207E-5 x DAP3)). Statistically, there is a regular correlation between total height (r=-0,200) and commercial height (r=-0,224) with the diameter of the trees.